Linking African and Western models through integration of trickster folktales in the application of Cognitive Behavior Therapy for depression - Nzewi, Esther N. (Psychology: the Journal of the Hellenic Psychological Society, 2020)
The unique re-entry challenges of African psychologists trained in western universities is evolving strategies for applying general clinical theories and therapeutic techniques in ways that are clinically effective and culturally sensitive. This case study presents the cross-cultural application of Cognitive Behavioral Theory (CBT) for the treatment of Major Depressive Disorder (MDD) with a 12-year-old Nigerian adolescent. Cultural relevance is enhanced by the integration of culture-based trickster folktales in the cross-cultural application of CBT. The strategies for identifying major themes, contents, contexts, the characteristics of the villains and victims, nature of interpersonal relationships, emotions, behavior and consequences in trickster folktales are described. The case study further demonstrates how these components of trickster folktales are used for the implementation of core therapeutic techniques of Cognitive Behavioral Therapy (CBT). The outcomes are discussed in terms of the benefits of the therapeutic application of CBT, efficacy of modified CBT in nonwestern countries, and client’s characteristics important in the treatment of Major Depressive Disorder with culturally modified CBT in adolescents.